The performance improvement of the combustion process in diesel engines with fuel heater - wagiman, Acep (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2024)
The incomplete combustion process will be a problem in the development effort of the diesel engine's performance. The non-homogeneous air-fuel mixing process is one of the factors which causes incomplete combustion. Heating the diesel fuel to a certain temperature before it goes through the high-pressure injection pump will lower its density and viscosity. Therefore, when injected in the combustion chamber, it forms smaller droplets of fuel spray which results in a more homogeneous air-fuel mixture. Moreover, using higher temperatures will make the diesel fuel easier to ignite to compensate for the limited time that is available in high-speed operating conditions. Diesel fuel heating can improve the combustion process to increase the power and decrease fuel consumption optimally.